Embracing not Erasing Contextual Variability in Children’s Behavior: Theory and Utility in the Selection and Use of Methods and Informants in Developmental Psychopathology - Dirks, Melanie A. (J Child Psychol Psychiatry, 2012)
This paper examines the selection and use of multiple methods and informants for the assessment of disruptive behavior syndromes and attention deficit/hyperactivity disorder (ADHD), providing a critical discussion of (a) the bidirectional linkages between theoretical models of childhood psychopathology and current assessment techniques; and (b) current knowledge concerning the utility of different methods and informants for key clinical goals. There is growing recognition that children’s behavior varies meaningfully across situations, and evidence indicates that these differences, in combination with informants’ unique perspectives, are at least partly responsible for inter-rater discrepancies in reports of symptomatology. Such data suggest that we should embrace this contextual variability as clinically meaningful information, moving away from models of psychopathology as generalized traits that manifest uniformly across situations and settings, and towards theoretical conceptualizations that explicitly incorporate contextual features, such as considering clinical syndromes identified by different informants to be discrete phenomena. We highlight different approaches to measurement that embrace contextual variability in children’s behavior and describe how the use of such tools and techniques may yield significant gains clinically (e.g., for treatment planning and monitoring). The continued development of a variety of feasible, contextually sensitive methods for assessing children’s behavior will allow us to determine further the validity of incorporating contextual features into models of developmental psychopathology and nosological frameworks.